The effect of language on trade: the Malaysian case. - Ismail, Normaz Wana (Universiti Malaysia Sarawak, 2010)
This study empirically investigates the relationship between common language and trade by fully utilized gravity model. The model is further augmented to identify whether Malay, Chinese and English language give significant impact on Malaysian bilateral trade with her eighty trade partners over the period 1980 to 2005. The result suggests that a country that have common in language will trade more each other as it can be an important means in reducing the information cost in trade. The result also revealed that besides English as the language of trade, the Chinese language is increasingly important in Malaysian bilateral trade, particularly within Asian countries.